METABOLIC FINGERPRINTING OF ROOT, STEM AND LEAF EXTRACTS OF PHYLLANTHUS AMARUS - Giri, Archana; Pammi, S.S.Sravanthi; TVS, Padmavathi (Journal of Phytology, 2016)
Â Phyllanthus amarus belonging to family Euphorbiaceae is an important medicinal plant from ancient times which is used in Chinese and Ayurvedic medicine. It is a small annual herb mostly found in Central and Southern India .All parts of this plant have medicinal value and are used in traditional medicines for curing various diseases such as jaundice, hepatitis B, C, microbial infections, viral diseases, tumors and kidney stones etc. Keeping in view its immense medicinal potential, phytochemical analysis was carried out using different solvents such as ethyl acetate, dimethyl formamide, chloroform, dichloromethane and n-Hexane. All the plant parts viz. root, stem and leaf were separately analyzed for the detection of phenols and flavonoids, of which leaf exhibited highest concentration compared to root and stem. Maximum percentage of phenols and flavonoids could be detected with dimethyl formamide in comparison to other solvents that were used in the study. Dimethyl formamide leaf extract displayed highest phenolic content of 40.75mg/g and highest flavonoid content of 51.5mg/g.